O documentar na educação infantil: uma revisão integrativa da literatura específica - Thuorst, Janaina (2024)
This dissertation stems from close engagement with the teaching context and an interest in enhancing pedagogical practices and contributing to the strengthening of the teaching group. Thus, the general objective of the study is to analyze the use of pedagogical documentation as a tool to enhance the processes of school inclusion. The investigative approach is qualitative, conducted through exploratory and descriptive research. A systematic review of scientific productions on the subject was carried out on the CAPES platform, covering the period from 2013 to 2023, given its indexing of a significant group of national and international databases and journals. Eleven articles were analyzed based on three analytical axes: Pedagogical documentation: practices and narratives; Pedagogical documentation and formative processes; Pedagogical documentation and school inclusion. Semi-structured interviews were conducted with three teachers, the school principal, and the special education teacher. The interviews were recorded, transcribed, and analyzed based on two main axes: Pedagogical documentation and inclusive processes: the perspective of the school team; Documenting and including. These axes explore understandings of inclusive processes related to pedagogical documentation. The findings reveal a scarcity of research exploring the relationship between pedagogical documentation and inclusive processes. Studies emphasize the fundamental role of documentation as a tool for recording and reflecting on pedagogical practices, valuing children's voices and agency while enabling meaningful learning experiences. This highlights the importance of research in this area, underscoring the need to expand knowledge and understanding of the topic. Regarding inclusive aspects, pedagogical documentation significantly contributes to overcoming stigmas by focusing on achievements rather than the final product. As a result, the study introduces the "Perspective of Observation" tool, aimed at helping teachers improve their ability to observe and document daily events, thereby recognizing children's learning processes. Although still in the implementation phase, the tool has been well-received by teachers, who report better comprehension of learning processes and an enhanced ability to identify individual needs.